IMPACTS OF COMMUNICATIVE TEACHING ON LEARNERS IN ENGLISH TEACHING - Zebiniso Bobonorova Faxriddin qizi (Galaxy International Interdisciplinary Research Journal, 2022)
At present, most people desire to improve their English skills or make their children fluent in English. There are many opportunities to learn English provided through various means such as formal education, travel, study abroad, and through the media and the Internet. The most important demand for English has created a great need for quality language education. For this, the way we teach and what is taught is more important than ever. Today, modern teachers who teach language students know a wide range of techniques and methods. The topic of this presentation also deals with one of the teaching methods - the Method of Communicative Language Approach.This publication seeks to explore the effectiveness of the use of teaching methods in English classrooms. Because it can improve students' understanding of the language. In addition, learning communication allows students to be more confident in communicating with other people, and they also enjoy talking more. The sample section contains detailed information on the relevance of English learning, the role of the teacher. In communication learning, the basic components of communication learning and the activities of learning related language .